Acute Viral Hepatitis in Men Having Sex with Men - Fernandez-Montero, José V.; Soriano, Vicente (AIDS Reviews, 2022)
For the past 5 years, all adults presenting with > 10-fold liver enzyme elevations at the emergency department of the largest hospital in Barcelona were tested for markers of acute viral hepatitis. Out of all positive tests, hepatitis B was detected in 28%, followed by hepatitis E (18%), hepatitis C (17%), and hepatitis A (14%), and only 1% had hepatitis D. The remaining 22% were associated with herpesvirus infections, mostly Epstein– Barr virus (14%) and cytomegalovirus (Llaneras et al. Clin Gastroenterol Hepatol. 2020).
Keywords: acute viral hepatitis; men; JCR